The Effector Function of Allergens - Hazebrouck, Stéphane; Canon, Nicole; Dreskin, Stephen C. (Frontiers in Allergy, 2022)
Allergens are antigens that generate an IgE response (sensitization) in susceptible individuals. The allergenicity of an allergen can be thought of in terms of its ability to sensitize as well as its ability to cross-link IgE/IgE receptor complexes on mast cells and basophils leading to release of preformed and newly formed mediators (effector activity). The identity of the allergens responsible for sensitization may be different from those that elicit an allergic response. Effector activity is determined by 1) the amount of specific IgE (sIgE) and in some circumstances the ratio of sIgE to total IgE, 2) the number of high affinity receptors for IgE (FcR1) on the cell surface, 3) the affinity of binding of sIgE for its epitope and, in a polyclonal response, the collective avidity, 4) the number and spatial relationships of IgE binding epitopes on the allergen and 5) the presence of IgG that can bind to allergen and either block binding of sIgE and/or activate low affinity IgG receptors that activate intracellular inhibitory pathways. This review will discuss these important immunologic and physical properties that contribute to the effector activity of allergens.